Fault rocks within the blueschist metabasalts of the Diamante–Terranova unit (southern Italy): potential fossil record of intermediate-depth subduction earthquakes - Vitale, Stefano; Fedele, Lorenzo; Tramparulo, Francesco D’Assisi; Prinzi, Ernesto Paolo (Geological Magazine, 2019)
Abstract We report the first evidence of fault rocks (FRs) developed during high-pressure/low-temperature (HP/LT) subduction-related metamorphism, within quartz+epidote pods embedded in the glaucophane–lawsonite-bearing ophiolitic metabasalts of the Diamante–Terranova unit (Calabria, Italy). FRs occur as relic injections appearing as thin dark seams, locally showing an internal foliation characterized by tabular, curvilinear and meander-like shapes, and consist of very fine grains of glaucophane and titanite, locally including survivor clasts of epidote and lawsonite. Some boudinaged veins show glaucophane fibres in the boudin necks, marking a clear HP/LT syn-metamorphic origin at c . 30 km depth. The injected FRs can be alternatively interpreted either as pseudotachylytes or as fluidized ultracataclasites. Although subsequent recrystallization largely obliterated primary diagnostic features, the occurrence of (i) different-coloured flow streaks, characterized by alternating layers of glaucophane and titanite, (ii) well-developed flow folds and (iii) corroded epidote survivor crystals could indicate a viscous flow of molten material characterized by a non-uniform chemical composition. With this in mind, we support the hypothesis that these fine-grained veins were originally pseudotachylytes generated by the frictional melting of the glaucophane-rich layers of the Diamante–Terranova metabasalts, likely related to seismic events occurring during the Eocene along thrust faults within the subducting oceanic Ligurian lithosphere. The lack of evidence for pseudotachylyte relics in the metabasalt source rock argues for a selective preservation, largely dependent on the efficient mechanical shielding action of the stiffer quartz+epidote pods.